Volatile Organic Compound Profiling from Postmortem Microbes using Gas Chromatography–Mass Spectrometry. Issue 1 (3rd September 2019) - Cernosek, Terezie; Eckert, Kevin E.; Carter, David O.; Perrault, Katelynn A.
Abstract: Volatile organic compounds (VOCs) are by‐products of cadaveric decomposition and are responsible for the odor associated with decomposing remains. The direct link between VOC production and individual postmortem microbes has not been well characterized experimentally. The purpose of this study was to profile VOCs released from three postmortem bacterial isolates ( Bacillus subtilis, Ignatzschineria indica, I. ureiclastica) using solid‐phase microextraction arrow (SPME Arrow) and gas chromatography–mass spectrometry (GC‐MS). Species were inoculated in headspace vials on Standard Nutrient Agar and monitored over 5 days at 24°C. Each species exhibited a different VOC profile that included common decomposition VOCs. VOCs exhibited upward or downward temporal trends over time. Ignatzschineria indica produced a large amount of dimethyldisulfide. Other compounds of interest included alcohols, aldehydes, aromatics, and ketones. This provides foundational data to link decomposition odor with specific postmortem microbes to improve understanding of underlying mechanisms for decomposition VOC production.